1990
DOI: 10.1007/bf02600406
|View full text |Cite
|
Sign up to set email alerts
|

The identification of psychiatric illness by primary care physicians

Abstract: Patients with a psychiatric illness who were relatively frequent users of the clinic were most likely to be identified by a physician as having a mental health problem. When psychiatric illness and utilization rates were statistically controlled, men and women had comparable identification rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We also asked them to report any personal history of psychopathology, including panic attacks and use of psychotropic medication. We excluded males because females report higher levels of anxiety and are more frequently diagnosed with panic disorder (Cleary, Burns, & Nycz, 1990). We then identified 79 females with an ASI score greater than 27, which is one standard deviation above the mean for college females (Peterson & Reiss, 1992).…”
Section: Participantsmentioning
confidence: 99%
“…We also asked them to report any personal history of psychopathology, including panic attacks and use of psychotropic medication. We excluded males because females report higher levels of anxiety and are more frequently diagnosed with panic disorder (Cleary, Burns, & Nycz, 1990). We then identified 79 females with an ASI score greater than 27, which is one standard deviation above the mean for college females (Peterson & Reiss, 1992).…”
Section: Participantsmentioning
confidence: 99%
“…Women were more likely to receive mental health misdiagnoses in initial primary care visits than were men, even after correcting for the higher epidemiologic rates of mental health problems among women.70,75,76 However, the difference in the rates of misdiagnoses for men and women disappeared after the third appointment, when physicians were better able to evaluate women's symptoms than they were initially. 75 In addition, the presence of emotion during medical encounters has been associated with misdiagnoses for women but not for men. 70 In an experimental study, two groups of randomly assigned internists were shown one of two silent videotapes with identically scripted dialogue of cardiac symptoms in subtitles.…”
Section: Perceptions Of Emotionmentioning
confidence: 99%
“…Women may require three visits and men one in order to separate mental health from organic problems. 75 Women are more likely to use primary care services for drug and alcohol problems because drug and rehabilitation services are intended primarily for men.G1 Women also suffer higher rates of sexual and physical abuse than do men, which often manifests as somatic symptoms that bring them to primary care settingsEsg5 Women suffer from more chronic conditions, e.g., diabetes, that require monitoring by primary care providers than men do. Women have higher rates of emotional disorders than men, and the majority seek care from primary providers.…”
Section: Questions About the Diagnostic Biasmentioning
confidence: 99%
“…The most alarming finding was that 55 percent received prescriptions for psychotropic medications (Bart & Grossman, 1976). More recent studies suggest that gender stereotypes continue to affect both primary care and psychiatric practice (Cleary, Burns, & Nycz, 1990;Redman, Webb, Hennrikus, Gordon, & SansonFisher, 1991;Townsend, 1995).…”
Section: Sexuality Nomenclature As Sexual Politicsmentioning
confidence: 95%